PROBLEMATIKA PEMBENTUKAN KESADARAN KRITIS PADA PNPM-MANDIRI PERKOTAAN (Studi Kasus di Kelurahan Sekaran, Kecamatan Gunungpati, Kota Semarang) - Luthfi, Asma (Faculty of Social Science, Universitas Negeri Semarang, 2013)
The nature of community development is to estabilish critical consciousness of society. In the process of community development through the PNPM-Mandiri Perkotaan, critical consciousness is expected to be formed through a series of empowerment activity cycle. This study used a qualitative approach to analyze data in a descriptive and inductive. This study showed that the process of community development PNPM-Mandiri Perkotaan can be seen in the cycle and the activities that actively involve the community and participatory, critical consciousness which is formed from each cycle that emphasizes the revitalization of the universal values of humanity and the basic principles of community , and a variety of opportunities and barriers in the formation of critical consciousness. But the critical consciousness formed by the PNPM-Mandiri Perkotaan still a functional and modernist paradigm, because only emphasizes the human aspect. Empowerment programs are less touched on structural aspects. This makes the process of empowerment in PNPM-Mandiri Perkotaan has not been able to solve the problem of society as a Â comprehensive.